KARAKTERISTIK BUBUK ALGA COKLAT (Sargassum polycystum) PADA PERLAKUAN UKURAN BAHAN DAN SUHU PENGERINGAN - Maulina, Shenni; Suhendra, Lutfi; Gunam, Ida Bagus Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
One of the natural resources found in the sea and can be utilized is Sargassum polycystum . Sargassum polycystum has a pigment content one of which is fucosantin. Fucosantin can be utilized the field of health is as antioxidant. In addition, fucosantin is the most dominant brown and carotenoid dye present that can be used as natural dyes. The aim of this research were to know the effect of size pieces and drying temperature on the color quality and antioxidant of brown algae powder and to determine the best size pieces and drying temperature to obtain color quality and antioxidant of brown algae powder. The experiment in this study uses factorial Randomized Block Design (RBD) with two factors treatment, the first factor is the size pieces of 3 levels 2 cm x 0.5 cm, 3 cm x 0.5 cm, 4 cm x 0.5 cm and the second factor is the temperature of the drying 3 levels 40±2°C, 45±2°C, 50±2°C. The result showed that the size pieces effect on total phenol and antioxidant capacity of brown algae powder. The temperature of the drying effect on water content, total phenolic and antioxidant capacity of brown algae powder. The size pieces and temperature of the drying not effect on intensity of color (L* a* b*). The result of this research showed that pieces size 4 cm x 0.5 cm and temperature of drying 45±2°C produce the best characteristics water content 12.86±8.83%, total phenolic 12.86±4.5 GAE/100g, antioxidant capacity 26.36±0.15 GAEAC/100g, intensity of brightness (L) 7.72±0.45, intensity of redness (a) -7.02±0.02, yellowish intensity (b) 40.88±0.77 Key words: Sargassum polycystum , Antioxidans Capacity, Total Phenol, Intensity of Color.